Tango and physiotherapy interventions in Parkinson’s disease: a pilot study on efficacy outcomes on motor and cognitive skills - Rabini, Giuseppe; Meli, Claudia; Prodomi, Giulia; Speranza, Chiara; Anzini, Federica; Funghi, Giulia; Pierotti, Enrica; Saviola, Francesca; Fumagalli, Giorgio Giulio; Di Giacopo, Raffaella; Malaguti, Maria Chiara; Jovicich, Jorge; et al. (Scientific reports, 2024)
Pharmacological treatments in Parkinson’s disease (PD), albeit effective in alleviating many motor symptoms, have limited effects in non-motor signatures as cognitive impairment, as well as in other aspects included postural instability. Consequently, complementary interventions are nowadays a prerogative of clinical practice managing PD symptomatology. In this pilot longitudinal study, we recruited twenty-four PD patients participating in one of two interventions: adapted Argentine Tango or group-based physiotherapy. Participants underwent a motor and neuropsychological evaluation before and after four months of activities, carried out twice a week. We found a general stabilization of motor and cognitive abilities, with significant improvements in several motor skills, mainly pertaining to static and dynamic balance, similarly in both groups. At cognitive level, we measured a significant improvement in both groups in the Action Naming task. Interestingly, only PD patients in the Tango group improved their performance in the test measuring facial emotion recognition. These findings highlight the crucial role that physical activities have in the stabilization and slowdown of disease’s progression in PD. They further highlight the beneficial effects of a group-based physical intervention, which, especially in the case of Tango, could lead to behavioral ameliorations in domains other than the motor, such as emotion recognition.